Vellgrove Avenue, Canning Vale - A Case Study of Rehabilitation – 20 year review - Leek, Colin (Australian Geomechanics Society, 2011)
In 1992, Vellgrove Ave in the City of Canning was selected for a trial using slag lime stabilisation of local limestone. Trial sections were constructed using a control section constructed with limestone sub-base, crushed granite road-base and thin asphalt surfacing, and two test sections, one with a slag-lime stabilised limestone sub-base with crushed granite road-base and the other with a limestone sub-base and slag-lime stabilised base course. The design life of the pavement sections was 20 years, which expires in 2012. This paper reports on the current condition and performance of the pavement as it nears the end of the design life.